BIOLOGIA FORENSE NA ESCOLA: APLICAÇÃO DE ATIVIDADE INTERATIVA PARA ALUNOS DO ENSINO BÁSICO - ANDRADE, Raul de Lima Soares,; VASCÃO, Andressa Aparecida Xavier,; MILITÃO, Fernanda Turini,; ALVES, Jonilda da Silva,; SILVA, Vitória Aires,; MORAIS, Glaucia de Almeida, (ANAIS DO ENIC, 2023)
-